Investigation of the Therapeutic Potential of Boric Acid in Enteritis-Induced Quails - Aslan, Sultan; Simsek, Ulku G.; Eroksuz, Hatice; Karagulle, Burcu; Eroglu, Mehmet; Incili, Gokhan K.; Incili, Canan A. (Wiley, 2025)
This study investigated the effects of boric acid added to feed and water on intestinal histopathology, immune parameters, and intestinal bacterial flora in experimentally enteritis-induced Japanese quails. Eighty-four quails were used in the study, which were divided into seven groups. The following groups were used in the study: control (G1), infected (G2), infected + antibiotic (G3), infected + boric acid added to feed (100 mg/kg) (G4), infected + boric acid added to feed (300 mg/kg) (G5), infected + boric acid added into water (100 mg/L) (G6) and infected + boric acid added into water (300 mg/L) (G7). Data were analysed using one-way ANOVA, and differences between groups were determined by Tukey's honestly significant difference test. The highest levels of white blood cells were found in the infection group, whereas the lowest levels were found in the control group (p < 0.05). Boric acid taken with water decreased the number of Enterobacteriaceae, Escherchia coli, and total mesophilic aerobic bacteria. However, these differences were not significant compared with the infection group (p > 0.05). Compared to the Infected group (G2), the most notable reductions in coliform counts were observed in the boric acid water 300 mg/L group (G7), which decreased from 3.29 to 2.90 log CFU/g (p < 0.01), and in the 100 mg/L group (G6), which showed a decrease to 2.93 log CFU/g (p < 0.01), In contrast, boric acid given in feed (G4 and G5) had no significant effect on any bacterial count compared to the infected group p > 0.05). Consequently, Effective results were observed when boric acid was added to drinking water, even with short-term (7 days) use. Boron derivatives could provide an effective alternative treatment option, especially in combating the growing antibiotic resistance.
Keywords: antibiotic; boric acid; enteritis; intestine; health